STARTUP PROFIT RATE PREDICTION SYSTEM USING MACHINE LEARNING ALGORITHMS (CAHIERS MAGELLANES-NS, 2024)
Startups are dynamic entities that contribute significantly to economic growth and innovation. Predicting their profit rate is crucial for investors, stakeholders, and entrepreneurs to make informed decisions. We introduce a new method employing machine learning algorithms to forecast startup profit rates. The study investigates various factors such as funding, market trends, and operational metrics to develop accurate prediction models. The findings showcase the effectiveness of machine learning methods in forecasting startup profit rates, offering valuable insights for stakeholders in the startup ecosystem, including investors and entrepreneurs.